Saving Souls, Enslaving Bodies: The Jesuits & African Slavery in Colonial Peru, 1580-1650. - Pickard, Duncan Mayher. (Tufts Archival Research Center, 2005)
This paper explores the Jesuits' African slave trade network between the port at Cartagena, Colombia, and the dozen sugar and wine plantations in coastal Peru, and the Jesuits' system of control over the African slaves on their plantations. I argue that Jesuits, while certainly not blameless in the cruelty of the slave trade, made space for black slaves in the Church in a way that sheltered traditions carried from Africa. By considering the example Jesuit slave plantations and the infrastructure that supported them, I wish to uncover the cracks in an incomplete system of Spanish colonial domination over African slaves.